Association of Domestic Violence and Early Suppression of lactation in Mothers Referring to Health Centers in Lahijan -Iran - Shahnaz Torkzahrani; Sanaz Fayazi; Marzieh Faghani Aghoozi; Malihe Amerian; Serveh Mohamadi; Mohadese Karimi Khoshal (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Domestic violence as a social factor has a significant role in the duration and quality of breastfeeding. Objectives: This study aims to determine association of domestic violence and early suppression of lactation in Mothers Referring to Health Centers in Lahijan- Iran. Methods: The present study is a retrospective case-control study. Participants included 235 mothers, 150 breastfeeding mothers and 85 mothers discontinued breastfeeding. Sampling was carried out by convenience and quota method in five urban health centers of Lahijan. The study tools were demographic information, domestic violence, and a researcher-made questionnaire to assess status of breastfeeding. Data were analyzed using Chi-square, t-test, Mann-Whitney test, and logistic regression by SPSS 16 software (P-value <0.05). Results: The average age of mothers was calculated to be about 27.97 years. According to the results of this study, mothers in the lactation group (group1) (93.33%) started breastfeeding more than esl group (group 2) (67.06%) (P<0.001). There was no statistically significant difference between the two groups in terms of unwanted pregnancy rate, cesarean section, and mothers' academic education (P-value> 0.05). The rate of psychological and physical violence in the group 1 was significantly higher than the group 1 and the chance of physical violence in group 2 was significantly (about 10 times) higher than the group1 (10, OR 001/0= P). Conclusion: It seems that physical and psychological domestic violence is directly associated with early suppression of lactation, so screening of domestic violence and appropriate interventions are recommended be considered in maternal care programs.